Artificial intelligence versus clinicians: systematic review of design, reporting standards, and claims of deep learning studies in medical imaging. - Nagendran, M; Chen, Y; Lovejoy, CA; Gordon, AC; Komorowski, M; Harvey, H; Topol, EJ; Ioannidis, JPA; Collins, GS; Maruthappu, M (BMJ Publishing Group, 2020)
Objective: To systematically examine the design, reporting standards, risk of bias, and claims of studies comparing the performance of diagnostic deep learning algorithms for medical imaging with that of expert clinicians.